The role of the loxP spacer region in P1 site-specific recombination. - Hoess, R H (1986)
The lox-Cre site-specific recombination system of bacteriophage P1 is comprised of a site on the DNA where recombination occurs called loxP, and a protein, Cre, which mediates the reaction. The loxP site is 34 base pairs (bp) in length and consists of two 13 bp inverted repeats separated by an 8 bp spacer region. Previously it has been shown that the cleavage and strand exchange of recombining loxP sites occurs within this spacer region. We report here an analysis of various base substitution mutations within the spacer region of loxP, and conclude the following: Homology is a requirement for efficient recombination between recombining loxP sites. There is at least one position within the spacer where a base change drastically reduces recombination even when there is homology between the two recombining loxP sites. When two loxP sites containing symmetric spacer regions undergo Cre-mediated recombination in vitro, the DNA between the sites undergoes both excision and inversion with equal frequency.